2008
DOI: 10.1016/s1726-4901(08)70168-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Therapeutic Lifestyle Program on Ultrasound-diagnosed Nonalcoholic Fatty Liver Disease

Abstract: Our data suggest that both 10-week diet-plus-exercise and exercise-only therapeutic lifestyle programs are effective for improving anthropometric indices, insulin sensitivity, ultrasound findings and physical fitness in ultrasound-diagnosed NAFLD patients. However, the range of improvement in patients on the diet-plus-exercise program is more obvious than that in patients on the exercise-only program. Moreover, the diet-plus-exercise program resulted in significant improvement in liver biochemistry, but the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 27 publications
2
60
0
Order By: Relevance
“…However, the oral hypoglycemic agents who were received by participants in both groups may have some effect on insulin resistance, the more profound improvement in insulin resistance in group (A) and the little non significant changes in group (B) proved that weight reduction was of great value to enhance the therapeutic pharmacological effects of oral hypoglycemic agents. Results of this study supported with many previous studies [11][12][13][14][15][16][17][18][19][20][21] . Adherence to combined dietary restriction and increased physical activity result in larger and progressive weight loss that can be maintained through the years 11 .…”
Section: Discussionsupporting
confidence: 92%
“…However, the oral hypoglycemic agents who were received by participants in both groups may have some effect on insulin resistance, the more profound improvement in insulin resistance in group (A) and the little non significant changes in group (B) proved that weight reduction was of great value to enhance the therapeutic pharmacological effects of oral hypoglycemic agents. Results of this study supported with many previous studies [11][12][13][14][15][16][17][18][19][20][21] . Adherence to combined dietary restriction and increased physical activity result in larger and progressive weight loss that can be maintained through the years 11 .…”
Section: Discussionsupporting
confidence: 92%
“…This study involved a multidisciplinary team for health screening and lifestyle modification implementation. Current knowledge suggests that diet and exercise lifestyle modification is effective and should be the first line of treatment for NAFLD [Harrison and Day, 2007;Suzuki et al 2005;Tamura et al 2005;Cankurtaran et al 2007;Chen et al 2008;Toshimitsu et al 2007]. Perhaps this type of approach could be of use in the future as a template for standardizing lifestyle modification in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from cross-sectional studies suggests that physical activity will likely reduce liver fat (29). However, we are aware of only three exercise studies in humans that have examined the effects of aerobic exercise on liver fat, and none of the studies has reported a significant effect (3,8,25). This is likely explained by the short duration (6, 10, and 12 wk) and small number of subjects in all three of these studies, which resulted in a limited exercise stimulus and a limited statistical ability to detect an effect.…”
Section: E1036 Effects Of Aerobic Vs Resistance Training On Ectopic Fatmentioning
confidence: 99%